Bone Microarchitecture and Biomechanics of the Necrotic Femoral Head. Issue 1 (December 2017) - Ma, Jian-xiong; He, Wei-wei; Zhao, Jie; Kuang, Ming-jie; Bai, Hao-hao; Sun, Lei; Lu, Bin; Tian, Ai-xian; Wang, Ying; Dong, Ben-chao; Wang, Yan; Ma, Xin-long
Abstract The mechanism behind osteonecrosis of the femoral head (ONFH) remains unclear. The aim of this study was to explore the pathogenesis of ONFH from a biomechanical standpoint to provide a theoretical basis for improved treatments. We compared the bone structure of fractured femoral heads with that of necrotic femoral heads by Micro-CT scanning and histological evaluation. In addition, we compared the biomechanical properties of each zone in fractured femoral heads with those in necrotic femoral heads by using biomechanical tests. Compared with fractured femoral heads, bone microarchitecture and bone morphometry in necrotic zone and sclerotic zone of necrotic femoral heads have altered markedly. In addition, the biomechanical properties of the necrotic zone in femoral heads weaken markedly, while those of the sclerotic zone strengthen. We hypothesize that discordance between bone structure and function of the femoral head may be involved in the pathogenesis of ONFH and that more attention should be paid to the prevention and treatment of such discordance.